2019
DOI: 10.1007/s40429-019-00239-1
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Marketing from 2014 to 2018: a Literature Review

Abstract: Purpose of Review Legislation and technology have led to unprecedented changes in the frequency and content of gambling marketing in many countries. We build upon previous reviews by exploring research on gambling marketing from between 2014 and 2018. Recent Findings Most literature reviewed was from the UK or Australia, with three key findings identified. First, gambling marketing is highly targeted and ubiquitous around sport, with the most popular strategies being increasing brand awareness, advertising com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 56 publications
4
74
0
4
Order By: Relevance
“…This aligns with the qualitative data theme of cynicism about the gambling industry, particularly participants' perceptions that industry advertising targets poorer populations who may be more susceptible to the false hope of escaping desperate socioeconomic situations. Recent studies on the impact of marketing indicate that riskier gamblers are more attuned to and thus impacted by advertising [for example ( 15 )], although Browne et al ( 16 ) found this effect across all types of gamblers. The density mapping data would also appear to confirm the notion of high environmental risk, with clusters of LGOs and FOBT machines disproportionately high in these areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with the qualitative data theme of cynicism about the gambling industry, particularly participants' perceptions that industry advertising targets poorer populations who may be more susceptible to the false hope of escaping desperate socioeconomic situations. Recent studies on the impact of marketing indicate that riskier gamblers are more attuned to and thus impacted by advertising [for example ( 15 )], although Browne et al ( 16 ) found this effect across all types of gamblers. The density mapping data would also appear to confirm the notion of high environmental risk, with clusters of LGOs and FOBT machines disproportionately high in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…These factors should be considered as potentially important contextual drivers of harm. This is further reflected in the rapidly changing environment in terms of advertising exposure and its impact that is being highlighted within the international literature, specifically on young people ( 14 ) and gambling populations more generally [for example, ( 15 , 16 )].…”
Section: Introductionmentioning
confidence: 99%
“…The association between GD and exposure to gambling marketing might be explained by disordered gamblers being more attentive to such marketing or being more likely to receive it due to their gambling history, or by exposure to gambling marketing contributing to the development of GD. The self-rated influence of gambling marketing is higher among those with GD and greater influence is typically reported in the form of increased gambling, gambling urges, or thoughts about winning in response to the marketing (Binde, 2014;Newall et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The landscape of gambling is changing rapidly in both land-based and online environments and gambling marketing, for example, is ubiquitous (Newall et al 2019). Arguably, the growing availability and commercialization of gambling are likely to create an environment in which adolescents are highly exposed to gambling (King et al 2010;Monaghan et al 2008).…”
Section: Introductionmentioning
confidence: 99%